2006
DOI: 10.1002/jnr.20802
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal neurodegeneration, spontaneous seizures, and mossy fiber sprouting in the F344 rat model of temporal lobe epilepsy

Abstract: The links among the extent of hippocampal neurodegeneration, the frequency of spontaneous recurrent motor seizures (SRMS), and the degree of aberrant mossy fiber sprouting (MFS) in temporal lobe epilepsy (TLE) are a subject of contention because of variable findings in different animal models and human studies. To understand these issues further, we quantified these parameters at 3-5 months after graded injections of low doses of kainic acid (KA) in adult F344 rats. KA was administered every 1 hr for 4 hr, for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
164
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 126 publications
(180 citation statements)
references
References 79 publications
16
164
0
Order By: Relevance
“…As majority of animals (>90%) exhibited >10 stages IV-V seizures during the 60 min after the 3rd KA injection, the 4th KA injection was reduced to 1.5 mg/kg b.w. Thus, each animal received a total KA dose of 10.5 mg/kg b.w., which is consistent with our recent study (Rao et al, 2006a). The motor seizures were characterized by unilateral forelimb clonus with lordotic posture (stage III seizures), bilateral forelimb clonus and rearing (stage IV seizures) and bilateral forelimb clonus with rearing and falling (stage V seizures).…”
Section: Animals and Kainic Acid Induced Acute Seizures And Status Epsupporting
confidence: 92%
See 1 more Smart Citation
“…As majority of animals (>90%) exhibited >10 stages IV-V seizures during the 60 min after the 3rd KA injection, the 4th KA injection was reduced to 1.5 mg/kg b.w. Thus, each animal received a total KA dose of 10.5 mg/kg b.w., which is consistent with our recent study (Rao et al, 2006a). The motor seizures were characterized by unilateral forelimb clonus with lordotic posture (stage III seizures), bilateral forelimb clonus and rearing (stage IV seizures) and bilateral forelimb clonus with rearing and falling (stage V seizures).…”
Section: Animals and Kainic Acid Induced Acute Seizures And Status Epsupporting
confidence: 92%
“…Although the frequency of seizures reported for different animal models of epilepsy in published reports varies considerably, rats exhibiting 3.0-3.5 seizures/8-h duration can be classified as rats with significant chronic epilepsy. However, in the same KA model, we have encountered rats with highly robust chronic epilepsy (8.0-12 seizures/8-h duration; Rao et al, 2006a). As this study represents our initial assessment of the effects of HFC grafting on chronic seizures, we chose rats with significant chronic epilepsy (instead of rats with highly robust chronic epilepsy) for all groups.…”
Section: Hfc Grafting Into the Hippocampi Of Chronically Epileptic Ratsmentioning
confidence: 99%
“…Furthermore, dendrites present on ectopic cells were excluded, as they were already located in the hilus. Others have demonstrated that aberrantly developing adult-born neurons stably integrate into the dentate circuitry (Scharfman et al, 2000;McCloskey et al, 2006) and that altered neurogenesis after SE is long lasting, with ectopic cells forming for many months after seizure induction (Rao et al, 2006;Jessberger et al, 2007). Thus, the extent of SE-induced neurogenesis abnormalities is likely even more severe than is suggested by our RV labeling.…”
Section: Discussionmentioning
confidence: 51%
“…Behavioral changes suggestive of motor seizures, normally observed after intraperitoneal injections of KA in non-anesthetized rats (Rao et al ., 2006c), were not seen in any of the rats receiving ICV KA injections under anesthesia. This is consistent with earlier observations that ICV KA administration, particularly at the low dose used in this study, does not produce motor seizures but consistently leads to hippocampal neurodegeneration (Shetty & Turner, 1999a,b;Shetty et al ., 2003Shetty et al ., , 2004Shetty et al ., , 2005b.…”
Section: Resultsmentioning
confidence: 99%